The privatisation of pilotage services: a panacea for South Africa’s pilotage ills? - Balmuth, Simon Mark (Shipping Law Unit, 2015)
Does the creation of a deemed servant-master relationship, between pilot and ship-owner or master through section 76 (2) of the National Ports Act (hereafter the NPA); accurately reflect the de facto relationship in which the parties stand? Can the provision's importation of the doctrine of vicarious liability and consequent foisting of liability on the ship-owner be defined as logical, just and practical? It will be argued after having had recourse to the manner in which these roles have come to be defined and understood in South African labour jurisprudence, the governing law, respective positions occupied by ship-owner and port authority, broad-based considerations of policy, and key tenets of the rationale underpinning the concept of vicarious liability; that the answer to the above-raised questions is are sounding no. In addition, the writer will submit that the privatisation of pilotage services presents a solution, alternate to the irrational imposition of the doctrine of vicarious liability, which is palatable to government, ship-owning interests and pilot. a) Introduction Typically, claims arising from consequences of pilot error satisfy the definition of a 'maritime claim' contained in s 1 (1) (e) and s 1 (1) (l) of the Admiralty Jurisdiction Regulation Act. As a result thereof; a South African court sitting in admiralty has jurisdiction to hear such claims. As to the identification of the appropriate law; s 6 (2) dictates that South African statute, if relevant, trumps pre-existing English admiralty law and is the law to be applied. The NPA, chiefly through sections 75 and 76, regulates the extent of the pilot's liability for his/her acts or omissions whilst a vessel is under compulsory pilotage. Thus, the Act is applicable to disputes arising from pilot error, before a South African court sitting in admiralty.